Comparison of Cognitive Learning Outcomes Among Eighth-Grade Junior High School Students Using Monopoly Games and Pop-up Books as Educational Media in ASEAN Social Studies - Edison Edison; Aman Aman (STAI Hubbulwathan Duri, 2024)
This study investigates the comparative effectiveness of two educational media—Monopoly game media and Pop-up Books—on cognitive learning outcomes in social studies, specifically ASEAN material, among class VIII students at SMP Negeri 1 Talang Ubi. Interactive media like Monopoly games are hypothesized to better engage students and enhance understanding compared to traditional Pop-up Books. A quasi-experimental design was employed, with class VIII students as the study population. Using purposive sampling based on pretest scores, class VIII.7 was designated as the experimental group using Monopoly games, while class VIII.2 served as the control group using Pop-up Books. Cognitive learning outcomes were measured through validated and reliable cognitive tests. Data were analyzed using a t-test to compare the effectiveness of the two instructional media. The t-test analysis revealed a significant improvement in cognitive outcomes for the experimental group compared to the control group. Students who utilized Monopoly game media demonstrated higher cognitive learning gains, suggesting enhanced engagement and understanding of ASEAN material. The findings suggest that interactive educational games, such as Monopoly, can more effectively enhance cognitive learning in social studies compared to traditional methods like Pop-up Books. This may be attributed to the engaging and participatory nature of game-based learning. Interactive game-based educational tools hold significant potential for improving student learning outcomes in social studies. Educators are encouraged to consider integrating such tools to foster better cognitive engagement and learning effectiveness in similar educational contexts.